Effect of Compressive Strength and Tensile Strength Value on Fiber Concrete Using Bendrat Wire Fibers - Yosia Clinton Purba; Johannes Tarigan; Nursyamsi Nursyamsi; Ricky Bakara (Publikasi Indonesia, 2024)
Concrete is a material used in modern construction and is a very important component in the manufacture of structures. Concrete has advantages, but also disadvantages, namely low tensile strength. To increase the tensile strength of concrete, fibers are added to the mix. One of the efforts made to increase the tensile strength of concrete is the addition of fibers to the fiber-concrete mixture. The purpose of this study is to examine the compressive strength and tensile strength values in fiber concrete if added with variations in fiber addition. An innovation in increasing the value of mechanical quantities in concrete is the use of bent wire fibers as a mixture in fiber concrete. This material is taken from former pieces in construction projects to connect steel reinforcement with Sengkang reinforcement and is also widely found in building shops. The fibers were also analyzed for microstructure using SEM (Scanning Electron Microstructure) tools. The length of this bent wire fiber is 13 mm with a diameter of 0.82 mm and has a minimum tensile strength value of 334.5 MPa. The variations in the addition of these bent wire fibers are 0%, 3%, 6%, and 9% of the total weight of the steel fiber. The soaking life of concrete is 7 days, 14 days, and 28 days. The results of this study show that the more variations in the addition of bent wire fibers, the compressive strength value of concrete and the tensile strength value of concrete will also increase. It can be seen that fiber concrete with an immersion life of 28 days with a variation of 9% added bent wire fiber has a maximum compressive strength value of concrete which is 63,645 MPa and a maximum value of tensile strength of 3,294 MP.